Sloth’s giant tick (Amblyomma varium) parasitizing free-ranging maned sloth (Bradypus torquatus) in the Atlantic Forest biome, Brazil. - Bernardes, Fernanda Coelho Simas (2022)
Amblyomma varium is a neotropical tick popularly known as the sloth’s giant tick, during the adult stage is found almost exclusively on mammals of the Bradypodidae and Megalonychidae families of the superorder Xenarthra. The maned sloth (Bradypus torquatus) is the only sloth species in danger of extinction in Brazil. This species is arboreal and descends to the ground only to perform defecation behavior. This behavior can be the determining factor for infestation and infection by different parasitic agents, including A. varium. This study reported the occurrence of A. varium found parasitizing free-living maned sloths (B. torquatus) in the Atlantic Forest biome of Northeast and Southeast Brazil. A total of 36 individuals were evaluated and more than 50% of the individuals were parasitized by ticks of the species A. varium. This study confirmed the importance of B. torquatus as a host for adults and nymphs of A. varium and reported the variation in length of the spurs on coxa IV of A. varium males.